Local and systemic effects in e-cigarette users compared to cigarette smokers, dual users, and non-smokers - Shanzina Iasmin Sompa; Jie Ji; Mizanur Rahman; Bengt Sjögren; Swapna Upadhyay; Koustav Ganguly; Anna-Carin Olin; Anna Bergström; Lena Palmberg (Respiratory Research)
Abstract Background The use of electronic (e)-cigarettes in the long term has been associated with an increased risk of respiratory diseases. Dual use of e-cigarettes and traditional cigarettes may increase these risks even more due to the combined exposure effects of these products. The aim of this study was to investigate the local and systemic effects of e-cigarette use for more than one year and compare them with healthy non-smokers, cigarette smokers, and dual users. Methods The clinical study was conducted among 22 healthy non-smokers, 20 e-cigarette users, 20 cigarette smokers, and 20 dual users. Participants were matched with age and BMI, had normal baseline lung function, and had no allergies. Exhaled FeNO and bronchial responsiveness were assessed along with reactive oxygen species (ROS), toll-like receptor (TLR) expression, and inflammatory cytokines in blood and sputum. Results Exhaled FeNO was higher in e-cigarette users (14 ppb, p = 0.04) and lower in cigarette smokers (9 ppb, p = 0.04) compared to healthy non-smokers (11 ppb). Bronchial responsiveness was increased in e-cigarette users (1.9 mg, p = 0.01) and cigarette smokers (1.9 mg, p = 0.01) compared to healthy non-smokers (2.9 mg). ROS in blood and sputum in e-cigarette users (p = 0.005 and p = 0.04) and dual users (p = 0.003 and p = 0.04) were increased. Also, TLR2 expression in blood granulocytes in all exposed groups (p = 0.001), TLR2 and TLR4 expression in sputum in e-cigarette users (p = 0.04 and p = 0.03) and dual users (p < 0.0001 and p = 0.004) were increased. Moreover, the percentage of IL13 and IFNγ cytokine-producing T cells in blood were increased in e-cigarette users (p = 0.0001 and p < 0.0001) and dual users (p = 0.001 and p < 0.0001). Conclusion Our research indicates that both local and systemic inflammatory responses, along with innate immune receptor activity, were significantly altered in e-cigarette users and dual users. Notably, these alterations were detected in e-cigarette users within a short timeframe of just 1 to 3 years of use. Clinical trial number Not applicable.